Crowd Work und Plattformökonomie Eine arbeitsrechtliche Fallstudie - Schneider-Dörr, Andreja (Arbeitsrechtliche Schriften, 2021)
This paper addresses the question of whether crowd workers on microtask platforms should be classified as employees. For years, this has been disputed from the perspective of labor law, but with a certain tendency to deny it. However, the BAG ruled in December 2020 that a crowd worker can be an employee by and large. So how are the circumstances to be assessed that make a crowd worker an employee (or non-employee)? That is what this paper investigates. In the first part of the paper, we review various empirical studies on crowd work and analyze the functioning of platforms. Economic and organizational sociology are also considered. In the second part, concrete case analyses from a self-experiment are presented in order to be able to evaluate them in terms of labor law. In the third part, two aspects are opened up, firstly, how the divergence between the national and the European legal concept of employee is again revealed in crowd work. On the other hand, new forms of regulation are suggested: For example, does Regulation P2B Regulation (2019/1150) not fit many of the problems of platform work? What about its applicability to platform work? What about "regulation by design"? Finally, it must be considered, how labor law can cope with new forms of work and, above all, forms of new organizational methods.